The Supply Chain Effects of Bankruptcy - Yang, S. Alex; Birge, John R.; Parker, Rodney P. (Management Science, 2015)
This paper examines how a firm’s financial distress and the legal environment regarding the ease of bankruptcy reorganization can alter product market competition and supplier–buyer relationships. We identify three effects—predation, bail-out, and abetment—that can change firms’ behavior from their actions in the absence of financial distress. The predation effect increases competition before potential bankruptcy as the nondistressed competitor behaves as if it has some first-mover advantage that could benefit a supplier with price control. The bail-out effect reflects the supplier’s incentive to grant the distressed firm concessions to preserve competition, improving supply chain efficiency and providing support for the exclusivity rule in Chapter 11 of the United States Bankruptcy Code when the supplier and the distressed firm are financially linked. The abetment effect is that the supplier may deliberately abet the competitor’s predation, leading to increased operational disadvantages for the distressed firm before bankruptcy. Together these effects stress that a firm’s bankruptcy potential can hurt its competitors and benefit its suppliers/customers. They also provide guidelines for firms’ operational decisions in such situations, a rationale for observed firm actions surrounding bankruptcies, and motivation for policies supporting reorganization and relaxing broad enforcement of nondiscriminatory pricing regulations. This paper was accepted by Serguei Netessine, operations management.